Incidence of injury based on sports participation in high school athletes. Issue 3 (2nd July 2016) - Kahlenberg, Cynthia A.; Nair, Rueben; Monroe, Emily; Terry, Michael A.; Edwards, Sara L.
ABSTRACT: Objectives : Youth participation in competitive athletics has significantly increased in the past two decades. There has also been a recent rise in the number of sports injuries that physicians are seeing in young athletes. The objective of this study was to assess the likelihood of sports injuries based on several risk factors in a general sample of athletes at a suburban-area high school. Methods : This was a cross-sectional study. An online survey was distributed to 2, 200 student-athletes at a local high school with a mean age of 15.9 years. Four hundred eighty four (22%) complete responses were received. Data collected in the survey included demographics, frequency of sports participation, level of participation, types of sports played, participation in cross-training, injuries incurred, use of non-steroidal anti-inflammatory drugs, and treatment for sports injuries. Results : Athletes played an average of 1.6 different sports. The average number of hours of participation in sports annually was 504.3 ± 371.6 hours. The average total number of sports injuries experienced by athletes in our study was 1.7 per participant. 80.8% of respondents reported having sustained at least one sports injury. A higher total number of hours per year of sports participation and playing a contact sport were significantly associated with more reported lifetime sports injuries. Older age, playing a contact sport, and playing on a travel/club team were associated with students using NSAIDs for sports injuries. Older age, playing a contact sport, and doing cross training are also associated with having had surgery for a sports injury. Conclusions : Although more hours of participation and playing a contact sport may lead to an increased number of injuries, this risk must be weighed against the myriad of benefits that sports provide for young athletes.